Inhibition of Enterovirus 71 (EV-71 infections by a novel antiviral peptide derived from EV-71 capsid protein VP1 - Tan, Chee Wah; Chan, Yoke Fun; Sim, Kooi Mow; Tan, Eng Lee; Poh, Chit Laa * (PLoS, 2012)
Enterovirus 71 (EV-71) is the main causative agent of hand, foot and mouth disease (HFMD). In recent years, EV-71 infections were reported to cause high fatalities and severe neurological complications in Asia. Currently, no effective antiviral or vaccine is available to treat or prevent EV-71 infection. In this study, we have discovered a synthetic peptide which could be developed as a potential antiviral for inhibition of EV-71. Ninety five synthetic peptides (15-mers) overlapping the entire EV-71 capsid protein, VP1, were chemically synthesized and tested for antiviral properties against EV-71 in human Rhabdomyosarcoma (RD) cells. One peptide, SP40, was found to significantly reduce cytopathic effects of all representative EV-71 strains from genotypes A, B and C tested, with IC50 values ranging from 6–9.3 mM in RD cells. The in vitro inhibitory effect of SP40 exhibited a dose dependent concentration corresponding to a decrease in infectious viral particles, total viral RNA and the levels of VP1 protein. The antiviral activity of SP40 peptide was not restricted to a specific cell line as inhibition of EV-71 was observed in RD, HeLa, HT-29 and Vero cells. Besides inhibition of EV-71, it also had antiviral activities against CV-A16 and poliovirus type 1 in cell culture. Mechanism of action studies suggested that the SP40 peptide was not virucidal but was able to block viral attachment to the RD cells. Substitutions of arginine and lysine residues with alanine in the SP40 peptide at positions R3A, R4A, K5A and R13A were found to significantly decrease antiviral activities, implying the importance of positively charged amino acids for the antiviral activities. The data demonstrated the potential and feasibility of SP40 as a broad spectrum antiviral agent against EV-71.